Covidaleyrodes flos, a new whitefly genus and species (Hemiptera: Aleyrodidae) infesting an endemic woody climber, Artabotrys speciosus (Magnoliales: Annonaceae) in the Andaman Islands, India - Dubey, Anil Kumar; Evans, Gregory A. (Zootaxa, 2025)
Covidaleyrodes flos, a new whitefly genus and species, is described from the Andaman Islands, India. Puparia of the new species were found in groups infesting the underside of the leaves of an endemic woody climber, Artabotrys speciosus (Annonaceae). Groups of male and female puparia were observed separately on different leaves. Images of the habitus, line drawings of the type specimens and SEM images of the new genus and species are provided. Affinities of the new genus with related genera are discussed and an identification key to puparia of related genera is provided.